Adsorption and immobilization of β-glucosidase from Thermoascus aurantiacus on macroporous cryogel by hydrophobic interaction - Mól, Paula Chequer Gouveia [UNESP]; Veríssimo, Lizzy Ayra Alcântara; Minim, Luis Antonio; Silva, Roberto da [UNESP] (My University, 2022)
Enzyme immobilization has been reported as a promising approach to improving parameters such as thermal stability, pH and reusability. In this study, a polyacrylamide cryogel functionalized with L-phenylalanine was prepared to be used in the adsorption of β-glucosidase from Thermoascus aurantiacus, aiming at its separation and also its immobilization on the cryogel matrix. The enzyme was produced by solid state fermentation. First, the adsorption was studied as a function of the pH and the resulting yield (Y, %) and purification factor (PF, dimensionless) were determined (1.57–5.13 and 64.19–91.20, respectively). The PF and yield from eluate samples obtained at pH 3.0 were the highest (5.13 and 91.20, respectively). Then, β-glucosidase was immobilized on the hydrophobic cryogel and the recovery activities (%) were determined as a function of temperature and in the presence of different saline solutions. The values ranged from 14.45 to 45.97. As expected, salt type and ionic strength affected the activity remained in the immobilized β-glucosidase. The average bioreactor activity was 39.9 U/g of dry cryogel and its operational stability was measured, with no decrease in activity being observed during seven cycles. Kinetic parameters of free and immobilized enzyme were determined according to different models.
Keywords: Adsorption; cryogel; hydrophobic interaction; L-phenylalanine; β-glucosidase